2023
DOI: 10.3389/fimmu.2023.1174020
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in long-COVID and its association with persistent dysregulation in inflammatory markers

Abstract: ObjectiveTo analyze the potential impact of sociodemographic, clinical and biological factors on the long-term cognitive outcome of patients who survived moderate and severe forms of COVID-19.MethodsWe assessed 710 adult participants (Mean age = 55 ± 14; 48.3% were female) 6 to 11 months after hospital discharge with a complete cognitive battery, as well as a psychiatric, clinical and laboratory evaluation. A large set of inferential statistical methods was used to predict potential variables associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 55 publications
0
1
1
Order By: Relevance
“…An evaluation of the plasma metabolome of patients with PCC showed alterations in metabolites related to mitochondrial dysfunction, 2 years after SARS-CoV-2 infection, indicating metabolic alterations persistence ( 14 ). Furthermore, cognitive symptoms are highly prevalent in people with PCC, but in a previous study with the same cohort, we failed to find clear association between systemic inflammation and the specific neuro-cognitive alterations ( 15 ).…”
Section: Introductioncontrasting
confidence: 58%
“…An evaluation of the plasma metabolome of patients with PCC showed alterations in metabolites related to mitochondrial dysfunction, 2 years after SARS-CoV-2 infection, indicating metabolic alterations persistence ( 14 ). Furthermore, cognitive symptoms are highly prevalent in people with PCC, but in a previous study with the same cohort, we failed to find clear association between systemic inflammation and the specific neuro-cognitive alterations ( 15 ).…”
Section: Introductioncontrasting
confidence: 58%
“… 42 ) Education is associated with long-term cognitive performance. 43 , 44 ) The number of formal years of education completed by individuals is positively associated with cognitive function throughout adulthood and predictive of a lower risk of dementia in later stages of life. 45 ) A study conducted in China showed a decreasing risk for each year of education (β=-0.098, p=0.013), whereas a study in New York showed that an education level of <12 years was a significant risk factor for long-term reduced cognitive performance after COVID-19 (OR=5.21; 95% CI 2.25–12.09).…”
Section: Discussionmentioning
confidence: 99%
“…In the available literature, it is possible to find data showing that “long COVID” symptoms were reported by up to 80% of patients, irrespective of the severity of the disease, but were more common in patients who required hospitalization [ 14 ].…”
Section: Discussionmentioning
confidence: 99%